2023
DOI: 10.1155/2023/9150324
|View full text |Cite
|
Sign up to set email alerts
|

Combined Network Pharmacology and Molecular Docking to Verify the Treatment of Type 2 Diabetes with Pueraria Lobata Radix and Salviae Miltiorrhizae Radix

Abstract: Objective. To explore the potential molecular mechanism of Pueraria Lobata Radix (RP) and Salviae Miltiorrhizae Radix (RS) in the treatment of type 2 diabetes mellitus (T2DM) based on network pharmacology and molecular docking. Methods. The chemical constituents and core targets of RP and RS were searched by Traditional Chinese Medicine System Pharmacology (TCMSP); target genes related to T2DM were obtained through GeneCards database, component target network diagram was constructed, intersection genes of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Molecular docking is a method of drug design based on the characteristics of receptors and the interaction between receptors and drug molecules. In recent years, molecular docking has become an important technology in the field of computer-aided drug research 66 , 67 . In the present study, it has been demonstrated that the 4 active components of SS , isobrucine, stigmasterol, (+)-catechin and brucine, could bind to the 6 core protein targets in varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular docking is a method of drug design based on the characteristics of receptors and the interaction between receptors and drug molecules. In recent years, molecular docking has become an important technology in the field of computer-aided drug research 66 , 67 . In the present study, it has been demonstrated that the 4 active components of SS , isobrucine, stigmasterol, (+)-catechin and brucine, could bind to the 6 core protein targets in varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently applied a minimum interaction score threshold of 0.4, followed by utilization of cytoscape and the MCODE algorithm to identify the central network and hub genes [ 29 , 30 ]. A higher interaction score indicated a more definite protein-protein relationship; an interaction score of 0.4 was the default parameter in the STRING database, and most previous research had been screened using this as the threshold [ 31 , 32 ]. The LASSO analysis is a dimensionality reduction algorithm that exhibits superior performance compared to regression analysis [ 33 ].…”
Section: Methodsmentioning
confidence: 99%